SYNCHRONIZATION OF LEARNING OUTCOMES IN LEARNING MANAGEMENT SYSTEMS AND LEARNING CONTENT MANAGEMENT SYSTEMS (Scientific Journal of the Dragomanov Ukrainian State University Series 2 Computer-Oriented Learning Systems, 2025)
In the modern context of educational digitalization, the issue of effectively managing the learning process, particularly using electronic platforms, has become especially relevant. The rapid advancement of technology and the growing need for distance learning have led to the widespread adoption of Learning Management Systems (LMS) and Learning Content Management Systems (LCMS) in higher education institutions. These tools are designed to provide convenient access to learning materials, monitor students’ progress, and automate the recording of their performance. However, in practice, challenges often arise regarding terminology alignment, duplication of functions across different systems, and technical data integration, which becomes especially evident when multiple software solutions are used simultaneously within the same institution. This study aims to analyze the functional capabilities of LMS, LCMS, and CMS, to compare them, and to develop and implement a prototype system for synchronizing academic results, using the example of integrating the MOODLE system with the internal system "PS Academic Performance Journal" (developed by Politek-Soft LLC). The article describes the architecture of the proposed solution, implemented using Java, the Spring Boot framework, and MySQL and Firebird databases. Attention is paid to the technical aspects of building the integration module, working with multiple databases, implementing periodic update mechanisms, and storing data in an intermediate table for further processing. The proposed solution has undergone successful testing using real database dumps and has demonstrated stable operation. The results suggest the potential of this approach for automating the synchronization of assessments within blended learning systems. Future research may focus on integrating with other educational platforms, implementing two-way data exchange, and supporting a wide range of learning activity types.
Keywords: content management systems; learning management systems; learning content management systems; data synchronization; blended learning